Culture and trust in technology-driven organizations - Alston, Frances (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'Preface Changes in the global business environment have drastically increased demands on businesses in the areas of productivity, product quality, innovation, and product development. Competing in a global environment has increased the need for enhanced communication exchanges, creating trusting cultures, and the ability to cope with the increased complexity and uncertainty of the ever-changing business environment. It is widely recognized that culture and trust play important roles in the corporate environment and must be managed in order to recruit and retain talented workers and build high-performing organizations. Managers have a need to understand the relationship between culture and trust and the role each plays in the successful creation of high-performing organizations. Authors and theorists have linked trust with increased performance levels, increased creativity, and increased critical thinking. These factors are critical for leaders to tap into when work is being performed in flexible and adaptive environments. Many researchers, authors, and theorists have contributed to developing the theories of culture and trust and have pointed out the important role that culture can play in the success of organizations. Presented in three parts, this book is written for the theorist, the researcher, and the practitioner. Section I outlines the literature on organizational trust and culture and the role theorists believe they play in the success of a changing domestic and global business environment. In conducting the literature review, various elements or attributes of culture and trust were studied'--
Includes bibliographical references (page 155-157) and index.
Keywords: Trust; Corporate culture; High technology industries